OVARIAN OVERDRIVE: FUNCTIONING GONADOTROPH ADENOMA LEADING TO SPONTANEOUS OVARIAN HYPERSTIMULATION - Mustapha, Khairul Azman; Yahya, Norhayati; Roslan, Teh Roseleen Nadia; Borhan, Marisa Khatijah (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Functioning gonadotroph adenomas (FGAs) are rare pituitary tumours characterised by the hypersecretion of biologically active gonadotrophs. We report a case of a 22-year-old Malay female diagnosed with FGA with ovarian hyperstimulation syndrome (OHSS), highlighting her clinical presentation, management, and post-operative outcomes. CASE The patient first presented at age 19 with acute abdominal pain and irregular menstruation. An abdominal ultrasound showed large bilateral multiloculated ovarian cysts, the largest cyst measuring 12 x 15 cm. She underwent laparotomy for left salpingo-oophorectomy and right ovarian cyst aspiration with histopathological examination (HPE) that ruled out ovarian malignancy. Post-operatively, she remained amenorrheic with a thin endometrial wall despite progestin therapy. Follow-up scans showed persistent large ovarian cysts. Hormonal work-up revealed elevated estradiol (13,422 pmol/L, NR 110–1468 pmol/L), unsuppressed FSH (31.8 IU/L, NR 3–8 IU/L) and raised prolactin (1551 mIU/L, NR 70–566 mIU/L) levels. She also had intermittent headaches but no visual disturbances, galactorrhea or hirsutism. MRI of the pituitary reported pituitary macroadenoma (1.8 x 2.6 x 2.9 cm) with suprasellar extension compressing onto the optic chiasm. The patient successfully underwent transsphenoidal surgery (TSS) of the pituitary adenoma. Tissue HPE stained positive for synaptophysin (+), FSH (+) and LH (+), with a low Ki-67 index of 0.1%, confirming the diagnosis of FGA with stalk effect. Post-TSS, her gonadotropin level normalised, menstruation resumed and ovarian cyst size decreased. Follow-up MRI showed no residual tumour or recurrence. CONCLUSION FGAs are a rare differential diagnosis that needs to be considered in females presenting with spontaneous OHSS, accompanied by elevated serum estradiol and unsuppressed FSH. Early diagnosis and prompt transsphenoidal surgery can restore normal menstruation, improve fertility, and potentially avoid ovarian surgery.